New method for estimating the economic penalties of ferrous scraps in the steelmaking industry due to material degradation during its storage in scrap yards. (27th May 2020) - Vicente, Asier; Picon, Artzai; Barco, Estibaliz
ABSTRACT: The ever-increasing pressure on the steelmaking industry to reduce its environmental footprint and achieve higher performance ispushing the sector to continuous improvement of its processes, This new paradigm places steel scrap recycling-based manufacturingprocesses as one of the main alternatives for the steelmaking industry. Using heterogeneous recycled scrap mixtures for producing new andhigher performance steel products requires the use of well characterized scrap to reduce uncertainties of the process. However, ferrousscrap might be stored for long periods of time in scrap yards and be affected by atmospheric corrosion that degrades its initial quality. Inthis paper a new empirical methodology is proposed, which helps quantify the influence of this degradation phenomenon on the Electric ArcFurnace (EAF) performance based on the Value In Use (VIU) of the scrap. The equations proposed allow estimating the extra cost induced bydegradation of ferrous scrap material during storage periods.